Literatures of Urban Possibility
XV, 281 p. 7 illus., 5 illus. in color.
Keywords: This book demonstrates how city literature addresses questions of possibility. In city literature, ideas of possibility emerge primarily through two perspectives: texts may focus on what is possible for cities, and they may present the urban environment as a site of possibility for individuals or communities. The volume combines reflections on urban possibility from a range of geographical and cultural contexts—in addition to the English-speaking world, individual chapters analyse possible cities and possible urban lives in Turkey, Israel, Finland, Germany, Russia and Sweden. Moreover, by engaging with issues such as city planning, mass housing, gentrification, informal settlements and translocal identities, the book shows imaginative literature at work outlining what possibility means in cities.